Mid-Term Safety and Efficacy of the Modified Double Hydrodistention Implantation Technique (HIT), Termed Systematic Multi-Site HIT (SMHIT), for Patients with Primary Vesicoureteral Reflux - Nakamura S (Research and Reports in Urology, 2020)
Shigeru Nakamura,1 Kazuya Tanabe,1 Taiju Hyuga,1,2 Taro Kubo,1 Satoru Inoguchi,1 Shina Kawai,1 Hideo Nakai1 1Department of Pediatric Urology, Jichi Medical University, Children’s Medical Center Tochigi, Shimotsuke, Japan; 2Department of Developmental Genetics, Institute of Advanced Medicine, Wakayama Medical University (WMU), Wakayama, JapanCorrespondence: Shigeru NakamuraDepartment of Pediatric Urology, Jichi Medical University, Children’s Medical Center, 3311-1, Yakushiji, Shimotsuke, Tochigi 329-0498, JapanTel +81-285-44-2111Fax +81-285-44-8452Email naka251148@gmail.comPurpose: To evaluate the treatment outcomes and postoperative complications associated with the systematic multi-site hydrodistention implantation technique (SMHIT) for primary vesicoureteral reflux (VUR) and to determine its mid-term efficacy and safety.Patients and Methods: We retrospectively reviewed the data for 17 ureters from 12 consecutive children, aged ≥ 1 year, with grade II–IV reflux and a history of febrile urinary tract infections (FUTI), who underwent a single-session of SMHIT. The primary outcome was the absence of postoperative FUTI (clinical success). The secondary outcome was improvement in reflux to grade 0–I on postoperative voiding cystourethrography (radiographic success).Results: Five and 7 children had bilateral and unilateral reflux, respectively. Reflux was categorized as grade II, III, and IV reflux in 2, 12, and 3 ureters, respectively. Seven of 10 (70%) toilet-trained children had bladder-bowel dysfunction (BBD) preoperatively. The SMHIT was performed for all patients, after which BBD improved. The mean postoperative follow-up period was 6 years and 9 months. The clinical success rate was 100%. Radiographic success was achieved in 16/17 ureters (94%) at 3– 4 months, 17/17 (100%) ureters at 1 year, and 17/17 (100%) ureters at 3 years postoperatively. Major complications did not develop postoperatively.Conclusion: When prioritizing treatment of concomitant BBD in children with primary VUR and avoiding dextranomer/hyaluronic acid injection therapy in contraindicated children according to the Food and Drug Administration recommendations, a single-session of SMHIT may be as effective and safe in the mid-term as performing open anti-reflux surgery.Keywords: dextranomer hyaluronic acid, Dx/HA, endoscopic treatment, vesicoureteral reflux